The Aino 3.0 model - Aino Silvo; Fabio Verona (Bank of Finland, 2020)
In this paper we present Aino 3.0, the latest vintage of the dynamic stochastic general equilibrium (DSGE) model used at the Bank of Finland for policy analysis. Aino 3.0 is a small-open economy DSGE model at the intersection of the recent literatures on so-called TANK ('Two-Agent New Keynesian') and MONK ('Mortgages in New Keynesian') models. It aims at capturing the most relevant macro-financial linkages in the Finnish economy and provides a rich laboratory for the analysis of various macroeconomic and macroprudential policies. We show how the availability of a durable consumption good (housing), on the one hand, and the presence of credit-constrained households, on the other hand, affect the transmission of key macroeconomic and financial shocks. We also illustrate how these new transmission channels affect model dynamics compared to the previous model vintage (the Aino 2.0 model of Kilponen et al., 2016).
URN:NBN:fi:bof-202005262152
Keywords: E21; E32; E44; F41; R31; 330; business cycles; small open economy; credit constraints; housing market; long-term debt